2013
DOI: 10.1371/journal.pone.0074151
|View full text |Cite
|
Sign up to set email alerts
|

The Gustin (CA6) Gene Polymorphism, rs2274333 (A/G), as a Mechanistic Link between PROP Tasting and Fungiform Taste Papilla Density and Maintenance

Abstract: Taste sensitivity to PROP varies greatly among individuals and is associated with polymorphisms in the bitter receptor gene TAS2R38, and with differences in fungiform papilla density on the anterior tongue surface. Recently we showed that the PROP non-taster phenotype is strongly associated with the G variant of polymorphism rs2274333 (A/G) of the gene that controls the salivary trophic factor, gustin. The aims of this study were 1) to investigate the role of gustin gene polymorphism rs2274333 (A/G), in PROP s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
145
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(155 citation statements)
references
References 80 publications
9
145
1
Order By: Relevance
“…The selected studies indicate that receptors of and sensitivity to bitter taste are reduced along life, resulting in a low tolerance threshold among children [48,43,46]. Regarding gender, three articles reported that women are more sensitive to bitter taste also during pregnancy [22,23,43], and one did not find differences between genders regarding the number of gustatory papillae [50]. Different genetic expression, mainly of TAS2R38 and changes in the sensitivity to bitterness sensitivity, have been reported, influencing eating behavior and food preference, including alcohol ingestion [52,53,62].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The selected studies indicate that receptors of and sensitivity to bitter taste are reduced along life, resulting in a low tolerance threshold among children [48,43,46]. Regarding gender, three articles reported that women are more sensitive to bitter taste also during pregnancy [22,23,43], and one did not find differences between genders regarding the number of gustatory papillae [50]. Different genetic expression, mainly of TAS2R38 and changes in the sensitivity to bitterness sensitivity, have been reported, influencing eating behavior and food preference, including alcohol ingestion [52,53,62].…”
Section: Resultsmentioning
confidence: 99%
“…Melis et al 2013 [50] Not find any difference between genders, mainly regarding the quantitation of gustatory papillae located on the tongue Bitterness perception and genetics Boxer et al…”
Section: Bitterness Perception and Other Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several molecular mechanisms underlying hyperguesia have been proposed. Polymorphism in the gene for carbonic anhydrase VI, which is highly expressed in the salivary glands and secreted into saliva, has been demonstrated to be associated with individual differences in PROP bitterness and also with fungiform papilla development and maintenance (17,(39)(40)(41)(42), although a recent report has failed to confirm this correlation (43). Salivary peptides belonging to the basic proline-rich protein family have also been implicated in contributing to PROP responsiveness (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previously reported phenotype-genotype relationships ranging from 55% to 85%. 13,38 Other factors including the number of fungiform papillae 14,39 and TAS2R38 receptor mRNA expression in taste cells 40 may play a role in defining PROP phenotypes.…”
Section: Discussionmentioning
confidence: 99%